Health-Related Quality of Life and Psychological Outcomes in Participants with Symptomatic and Non-Symptomatic Knees after ACL Reconstruction - Johanna M. Hoch; Ansley Swann; Rachel Kleis; Matthew C. Hoch; Carrie Baker; Dee Dlugonski (North American Sports Medicine Institute, 2024)
# Background Individuals who sustain an ACL injury and undergo reconstruction (ACLR) are at risk for the development of osteoarthritis. Recent investigations have applied the Englund criteria to categorize people with a history of ACLR as someone with a symptomatic or asymptomatic knee. # Purpose/Hypothesis The purpose of this study was to examine differences in health-related quality of life (HRQL) and psychological outcomes in people with a history of ACLR who were categorized as symptomatic or non-symptomatic by application of the Englund criteria. The authors' hypothesized participants classified as symptomatic would have lower HRQL, increased fear-avoidance beliefs, and decreased resilience compared to participants classified as non-symptomatic. # Study design Cross-sectional, survey # Methods Participants at least one-year after ACLR were recruited for the study and completed the Tegner Activity Scale, the Brief Resilience Scale (BRS), the modified Disablement in the Physically Active Scale (mDPA), and the Fear-Avoidance Belief Questionnaire (FABQ) at one time-point. Descriptive statistics were summarized using median \[interquartile range\] and differences between groups were examined using separate Mann-Whitney U tests. # Results Participants with symptomatic knees had a significantly higher BMI (24.8 \[6.4\]) than the non-symptomatic group (21.2 \[4.3\], p=0.013). Participants in the symptomatic group had worse HRQL on the physical subscale (12.5 \[16.3\] vs. 0.0 \[2.5\], p<0.001) and mental subscale (2.0 \[1\] vs. 0.0 \[1\], p=0.031), higher scores on the FABQ-Sport (14.5 \[11\] vs. 0.0 \[6\], p<0.001) and FABQ-Physical Activity (20 \[24\] vs. 1 \[4\], p<0.001) and less resilience (3.7\[0.42\] vs. 4.0 \[0.83\], p=0.028) compared to those participants in the non-symptomatic group. There were no differences in current physical activity (p=0.285) or change in physical activity (p=0.124) levels between the two groups. # Conclusions This series of differences may represent a cascade of events that can continue to negatively impact health outcomes across the lifespan for individuals with a history of ACLR. Future research should consider longitudinal investigations of these outcomes after injury and throughout the post-surgical and post-rehabilitation timeframe. # Level of Evidence Level 3b